PRINSIP CHECKS AND BALANCES DALAM SISTEM KETATANEGARAAN INDONESIA - Thaher, Irmanjaya (Gapenas Publisher, 2025)
The principle of checks and balances is an essential foundation of modern constitutionalism, preventing the concentration of power and ensuring accountability, transparency, and fairness in democratic governance, rooted in Montesquieu's idea of ??the separation of powers.This study analyzes the principle of checks and balances in the Indonesian constitutional system through four dimensions: the theoretical-constitutional foundation following the amendments to the 1945 Constitution, the role of the judiciary as a counterweight, the effectiveness of constitutional accountability mechanisms, and the identification of structural weaknesses to formulate an institutional strengthening agenda.The research methodology employed a Systematic Literature Review (SLR), conducted systematically, structured, and transparently to identify, evaluate, and synthesize relevant scholarly articles to gain a comprehensive understanding while minimizing bias.The results show that the amendments to the 1945 Constitution have transformed the architecture of checks and balances from executive dominance to proportional inter-branch equality. The Constitutional Court plays a vital role as a constitutional watchdog, but faces tensions between accountability and judicial independence. The impeachment mechanism and the protection of independent institutions such as the Corruption Eradication Commission (KPK) are crucial instruments, although their implementation faces the threat of political intervention that undermines the effectiveness of oversight.The research's conclusions emphasize the need for Pancasila-based reconstruction to strengthen the philosophical foundation of the balance of power system. A comprehensive institutional strengthening agenda is needed, encompassing strengthening the authority of the Regional Representative Council (DPD), protecting independent institutions, regulating proportional judicial accountability, and internalizing Pancasila values ??to optimize the effectiveness of checks and balances in preventing abuse of power and realizing a democratic, just, and sustainable Indonesian state system.